P322Structure and hemodynamics in the chick chorioallantoic membrane: Murray's law revisited. (15th July 2014) - Maibier, M; Nitzsche, B; Reglin, B; Hoepfner, M; Pries, AR
Abstract: Purpose: Although highly used as in vivo model to study e.g. angiogenesis and tumor development, topology and hemodynamics of the chick chorioallantoic membrane (CAM) vasculature has not been systematically characterized so far. Here, we investigated topological and hemodynamic network characteristics of the CAM by combining intravital microscopy and mathematical simulations. Methods: A day-14 CAM network was reconstructed from intravital microscopy recordings, providing information about vessel length, diameter (D) and location of over 4500 arterial and venular vessel segments. Data for flow velocity (v) and hematocrit (H) was determined in more than 80 vessels of different diameters in six CAM networks by using a spatial correlation approach (v) and spectral measurements (H). A mathematical simulation was used to calculate v, H, shear stress (τ) and pressure (p) for all vessel segments in the reconstructed network. Results: CAM topology exhibits a low degree of heterogeneity with a coefficient of variation (CV=SD/mean) of topological pathway length of 0.13 compared to 0.32 in rat mesentery (rm) and an inverse correlation of arterial and venous generation number for individual arterio-venous connections. Experimental measurements showed a nearly proportional increase of v with D for arteries (r 2 : 0.77) and veins (r 2 : 0.88). Consequently the variation of τ is relatively small (CV: 0.66 | CVrm : 1.45). Conclusions: Compared to a typical adult mammal network (e.g the mesentery) the CAM system exhibits a more regular and optimized design meeting the requirements of Murray's law. The principle of low cost realized in the organ responsible for the chick embryo's oxygen uptake and growth, the CAM, might indicate that a design according to Murray's law is relevant for functional optimization.